Hubungan Komunikasi Interpersonal anak dan Orang Tua dengan Motivasi Belajar Matematika Siswa Kelas V SDN 060838 Medan - Silalahi, Taruli Marito; Winny Sunfriska Limbong; Grace Cyntia Tarihoran (Universitas Sari Mutiara Indonesia, 2024)
The purpose of this study is to determine the relationship of interpersonal communication between children and parents on mathematics learning motivation of fifth grade students at state elementary school 060838 Medan in academic year of 2022/2023. This study is quantitative research. The population were fifth grade students. The sampling technique is total sampling, with a total of 20 students. The analytical method used is analyst prerequisite test, consisted of normality test, linearity test and the partial test (t-test). The Coefficients table shows that t-count value is 6.857 with a significance of 0.000 <0.05 and the t-table value is 1.729, with a significance of 0.05 and df = 20-1 = 19. Because sig 0.000 <0.05 and t-value 6.857 > t-table 1.729 then Ha is rejected and Ha is accepted. The correlation value is 0.850 and the coefficient of determination (R Square) is 0.723. The Adjusted R Square value is 0.708 and the standard Error of Estimate is 5.753. So it can be concluded that the contribution of interpersonal communication between children and parents affect mathematics learning motivation of fifth grade students at state elementary school is 85% and the remaining 15% is influenced by other factors. So it can be concluded that interpersonal communication between children and parents is related to students' mathematics learning motivation.